2017
DOI: 10.23917/forgeo.v31i1.3790
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Distribution of Landslides in Java and the Triggering Factors

Abstract: Java Island, the most populated island of Indonesia, is prone to landslide disasters. Their occurrence and impact have increased mainly as the result of natural factors, aggravated by human imprint. This paper is intended to analyse: (1) the spatio-temporal variation of landslides in Java during short term and long-term periods, and (2) their causative factors such as rainfall, topography, geology, earthquakes, and land-use. The evaluation spatially and temporally of historical landslides and consequences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…Previous research has applied GIS with overlay in different locations. Shahabi & Hashim (2015) employed GIS-based statistical models and remote sensing data with the overlay method to create a landslide susceptibility map in Cameron Highlands area of Malaysia, while Hadmoko et al (2017) overlaid annual isohyets to establish the distribution of landslide occurrence in Java that increases in every interval class, and the highest in 2500-3000 mm. Hartono & Nasikh (2017) employed map analysis using the intersect type of overlay with scoring to produce a landslide potency map of Batu-East Java.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has applied GIS with overlay in different locations. Shahabi & Hashim (2015) employed GIS-based statistical models and remote sensing data with the overlay method to create a landslide susceptibility map in Cameron Highlands area of Malaysia, while Hadmoko et al (2017) overlaid annual isohyets to establish the distribution of landslide occurrence in Java that increases in every interval class, and the highest in 2500-3000 mm. Hartono & Nasikh (2017) employed map analysis using the intersect type of overlay with scoring to produce a landslide potency map of Batu-East Java.…”
Section: Discussionmentioning
confidence: 99%
“…The main GISbased landslide capability in spatial contexts is spatial analysis in landslide digital maps. According to Hadmoko et al (2017) spatial analysis conducted landslides triggering from the causative factor. According to Guzzetti et al (2012) in an inventory map landslide information is shown as a combination of points, polylines, and polygons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulau Jawa merupakan wilayah dengan kepadatan penduduk tertinggi dan sangat rentan terhadap kejadian longsor, salah satunya yaitu Provinsi Jawa Barat. Berdasarkan inventarisasi data kejadian longsor, 67% kejadian longsor yang ada di Pulau Jawa terkonsentrasi di Provinsi Jawa Barat (Hadmoko et al, 2017). Berdasarkan data informasi bencana Indonesia dalam satu dekade terakhir (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019), rata-rata kejadian longsor per tahun di Jawa Barat cukup tinggi dengan jumlah mencapai 256 kejadian/tahun (BNPB, 2019).…”
Section: Pendahuluanunclassified
“…This was backed up by BPS (2020) data showing 77 flood cases and 17 landslide cases which indicated that there are human effects on land usage that does not accordance with its function. Therefore, land-use planning needs to pay serious attention to the regional capacity because changes in conservation areas such as deforestation cause flooding, landslides, and erosion (Appannagari, 2018;Hadmoko et al, 2017;Hamdani et al, 2014;Sejati et al, 2019).…”
Section: Introductionmentioning
confidence: 99%